Late Laborian trapezoids: Function and origin of the first transverse projectile tips of Western Europe prehistory. (30th October 2020) - Jacquier, Jérémie; Langlais, Mathieu; Naudinot, Nicolas
Abstract: Recently recognized as part of Final Lateglacial tool-kits, trapezoids remain enigmatic tools. The analytical part of this paper focuses on macro and micro-wear traces observed on Late Laborian trapezoids (GS1-Holocene transition, Atlantic facade) and their meaning from a utilitarian point of view. The consistency in the nature and organization of the traces leads us to interpret these implements as transverse projectile tips. These results confirm previous assumptions and establish the emergence of the Late Laborian trapezoids as an unprecedented innovation, marking a break from previous local weapon technology (points of piercing type and/or lateral inserts). These results provide a starting point to discuss the origin and significance of these artifacts. Their presence in different parts of Europe during the Lateglacial had been tentatively interpreted fifteen years ago as the result of large-scale cultural renewals in a context of progressively milder climatic and environmental conditions. At the current state of research, this diffusionist hypothesis suffers from a lack of geographic, techno-economic and functional continuity. Although techno-functional investigations inevitably raise the question of the target of these projectile points, current data do not provide a precise answer. It is however suggested that variations in stone points type during the Late Laborian was not necessarily related to prey type.